Competitive Limit Pricing Under Imperfect Information - Kyle Bagwell (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
This paper offers a new theory of limit pricing. Incumbents from different markets or regions "compete" against one another, with each attempting to price in a manner that deflects entry into the others' markets. An entrant is imperfectly informed as to the incumbents' respective investments in cost reduction and seeks to enter markets in which incumbents have high costs. In the focal equilibrium, the entrant uses a simple "comparison strategy," in which it enters only the highest-priced markets, and incumbents engage in limit-pricing behavior. The influence on pricing of the number of markets and the scope of entry is also reported. Finally, the theory indicates that limit pricing may in fact deter entry, with the entrant choosing to enter no market whatsoever. Throughout, the central feature of the analysis is that an incumbent's price affects its investment incentives, with lower prices being complementary to greater investment. Keywords: Limit Pricing, Entry Deterrence, Mixed Strategies, Endogenous Costs
Keywords: 330